2020
DOI: 10.13164/re.2020.0074
|View full text |Cite
|
Sign up to set email alerts
|

A Frequency and Polarization Agile Disc Monopole Wearable Antenna for Medical Applications

Abstract: A combined frequency and polarization reconfigurable textile based wearable disc monopole antenna is proposed in this paper. The antenna consists of a disc monopole as the radiator and four PIN diodes for realizing the agility property. By varying the different switching combination of the PIN diodes, frequency reconfigurability is achieved between the GSM and ISM band. Two circular polarization states, right hand circular polarization (RHCP) and left hand circular polarization (LHCP) are also realized in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After the optimization, it was found that the model was inaccurate when αα and ββ are fixed at constant values, however, γγ can be fixed at 0.5053. In order to make αα and ββ vary with change in parameter specification, let αα and ββ be as shown in Eq (10), respectively:…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…After the optimization, it was found that the model was inaccurate when αα and ββ are fixed at constant values, however, γγ can be fixed at 0.5053. In order to make αα and ββ vary with change in parameter specification, let αα and ββ be as shown in Eq (10), respectively:…”
Section: Plos Onementioning
confidence: 99%
“…An antenna's polarization reconfigurability depends on the current distribution and direction of flow on its surface [8,9]. Reconfigurable radiators [10], slot antennas [11], reconfigurable feeding networks [12,13], parasitic surfaces / meta-surface / partially reflecting surfaces [14,15] are some of the techniques employed. In the literature, there are several classical beam-steering approaches available: rotating dipole arms or rotating the antenna itself in the orthogonal plane, etc [16].…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [109], an L-shaped stub is introduced in the ground plane of a disc monopole antenna and a parasitic arc is placed around the main radiator. Two-pin diodes are placed between the main radiator and the parasitic arc to switch between two frequencies of 2.45 GHz and 0.92 GHz.…”
Section: Frequency and Polarization Reconfigurabilitymentioning
confidence: 99%
“…Fabricated prototype of the frequency and polarization-reconfigurable antenna on jean substrate in[109].…”
mentioning
confidence: 99%
“…In addition, polarized light has a strong anti‐interference ability due to its significant difference from natural light. These features enable the promising application potential of polarization detection in remote sensing imaging, [ 4–6 ] environmental monitoring, [ 7,8 ] astronomy, [ 9–11 ] 3D displays, [ 12–14 ] classified communications, [ 15–17 ] medical detection, [ 18–20 ] and some military applications. [ 21–23 ]…”
Section: Introductionmentioning
confidence: 99%